2019
DOI: 10.3389/fgene.2019.00796
|View full text |Cite
|
Sign up to set email alerts
|

Males, the Wrongly Neglected Partners of the Biologically Unprecedented Male–Female Interaction of Schistosomes

Abstract: Schistosomes are the only platyhelminths that have evolved separate sexes, and they exhibit a unique reproductive biology because the female’s sexual maturation depends on a constant pairing contact with the male. In the female, pairing leads to gonad differentiation, which is associated with substantial morphological changes, and controls among others the expression of gonad-associated genes. In the male, no morphological changes have been observed after pairing, although first data indicated an effect of pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 79 publications
(118 reference statements)
2
15
0
Order By: Relevance
“…Gene ontology enrichment analysis showed that hundreds of protein-coding genes related to neuron projection, differentiation, nervous system development, and G-protein receptor signaling pathways were present in the brown module ( Figure 7 and Supplementary File 4). This confirms that, both in S. mansoni and S. japonicum, sexually mature males have a more active neuronal regulation than sexually mature females, including those mediated by G-protein signaling, which might point to a higher importance of neuronal processes in males during reproduction [21]. We found that some module eigengenes had opposite patterns of change as a function of the days post-infection in males and females, such as in the brown module (Figure 6d).…”
Section: Differential Eigengene Network Analysis Reveals Different Pasupporting
confidence: 79%
“…Gene ontology enrichment analysis showed that hundreds of protein-coding genes related to neuron projection, differentiation, nervous system development, and G-protein receptor signaling pathways were present in the brown module ( Figure 7 and Supplementary File 4). This confirms that, both in S. mansoni and S. japonicum, sexually mature males have a more active neuronal regulation than sexually mature females, including those mediated by G-protein signaling, which might point to a higher importance of neuronal processes in males during reproduction [21]. We found that some module eigengenes had opposite patterns of change as a function of the days post-infection in males and females, such as in the brown module (Figure 6d).…”
Section: Differential Eigengene Network Analysis Reveals Different Pasupporting
confidence: 79%
“…7 and Supplementary Data 4). This confirms that, both in S. mansoni and S. japonicum, sexually mature males have a more active neuronal regulation than sexually mature females, including those mediated by G-protein signaling, which may point to a higher importance of neuronal processes in males during reproduction [21].…”
Section: Differential Eigengene Network Analysis Reveals Different Patterns Of Nervous System Differentiation In Males and Females Duringsupporting
confidence: 75%
“…The stimuli from the male worms play important roles in the growth and reproductive development of female worms [6], and these stimuli are independent of sperm transfer and fertilization [4,[7][8][9]. The male worms are proposed to deliver speci c molecules to female worms during pairing; the molecules associated this "magic male factor" have been unveiled in studies of the gynecophoral canal protein (GCP) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of S. japonicum have revealed that GCP is necessary for pairing to occur between male and female worms [24]. Although the biochemical activity of GCP has not yet been clearly de ned, there is accumulating evidence for its participation in male-female interaction in these worms [10].…”
Section: Introductionmentioning
confidence: 99%